Find ∫ (2x^5 - 1/(4x^3)-5) dx. giving each term in its simplest form.

with integration you need to increase the power and divide through by the new power for each term in the equation.2x5 goes to 2x6/6 = x6/3-1/(4x3) is equal to -x-3/4 which then goes to -x-2/4/-2 = x-2/8 = 1/8x2-5 goes to -5xwith integration a constant is also added to the end. this is due to the constant disappeareing during differentiation which is the reverse of integration.so the final solution is :x6/3 + 1/8x2 - 5x + c

Answered by Kieran Y. Maths tutor

5216 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate with respect to x: y=(6x^2-1)/2sqrt(x)


differentiate parametrically y=3t+4 and x=2t^2 +3t-5


How do I integrate tan^2 x?


Compute the integral of f(x)=x^3/x^4+1


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences